So Man Created Robot in His Own Image: The Anthropomorphism of Autonomous Weapon Systems and the Law of Armed Conflict - Sigrid Redse Johansen (Oslo Law Review)
Autonomous weapon systems have been widely debated throughout recent years. This article deals with autonomous weapon systems and the Law of Armed Conflict. Autonomous weapon systems are neither defined by international law, nor subject to specific regulation. The use of autonomous weapon systems must be in accordance with existing rules governing the conduct of hostilities. Among these rules are the principles of distinction and proportionality and the duty to take feasible precautions in attack. The assessment under these rules is subject to the discretion of the reasonable military commander. Somewhere in the decision cycle, the law requires a human assessment, which in turn can be labelled reasonable. The pending issue appears to be where in the decision cycle a human touch must be performed. In this article, I argue that autonomous weapon systems remain weapons and that they do not become humans, although we use human-like characteristics to describe them. Furthermore, I argue that because we call these weapon systems autonomous, we attribute them with human-like behaviour that they are not likely to possess in the near future, and subsequently that this attribution of human-like behaviour is not beneficial for our relationship to the machines or to the assessment of legality.